2015
DOI: 10.1021/am508071y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Atmospheric Atomic Layer Deposition of InxGayZnzO for Thin Film Transistors

Abstract: We have investigated the nucleation and growth of InGaZnO thin films by spatial atmospheric atomic layer deposition. Diethyl zinc (DEZ), trimethyl indium (TMIn), triethyl gallium (TEGa), and water were used as Zn, In, Ga and oxygen precursors, respectively. The vaporized metal precursors have been coinjected in the reactor. The metal composition of InGaZnO has been controlled by varying the TMIn or TEGa flow to the reactor, for a given DEZ flow and exposure time. The morphology of the films changes from polycr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 40 publications
2
50
0
Order By: Relevance
“…For example, amorphous indium gallium zinc oxide (IGZO) is appealing for high-volume TFT-display manufacturing, since it yields a tenfold higher electron mobility than amorphous silicon, in addition to improved performance even when fabricated at room temperature. 63,64 A very recent publication on the synthesis IGZO by AP-SALD is covered in Ref. 64.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, amorphous indium gallium zinc oxide (IGZO) is appealing for high-volume TFT-display manufacturing, since it yields a tenfold higher electron mobility than amorphous silicon, in addition to improved performance even when fabricated at room temperature. 63,64 A very recent publication on the synthesis IGZO by AP-SALD is covered in Ref. 64.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 A very recent publication on the synthesis IGZO by AP-SALD is covered in Ref. 64. Yet, when depositing higher-order multicomponent metal oxides, the co-injection method of producing doped ZnO may be challenging if, for example, one distinct precursor has a much higher reactivity or vapor pressure than the other.…”
Section: Discussionmentioning
confidence: 99%
“…This is why specific gate insulator materials should be chosen for specific semiconductor FETs to minimize the total carrier traps; for example, a‐SiO 2 is usually chosen for crystalline Si FETs and a‐SiN x :H for a‐Si:H TFTs. In contrast, AOS TFTs exhibit high performances with a wide variety of gate insulators such as SiO 2 , SiN x , SiO 2 /SiN x stacking layer, and high‐ k materials such as ZrO 2 , Y 2 O 3 , Al 2 O 3, and organic insulators (though there are some reports that some organic insulators cause extra instability) whose features benefit from the ionic bonding nature that hardly form electron traps.…”
Section: Instability Issues and Effects Of Carrier Traps In Aos Tftsmentioning
confidence: 99%
“…6 a-IGZO is considered a prime candidate for these applications due to its relatively high electron mobilities >10 cm 2 /Vs, 2 its good uniformity over large areas, its high optical transmission, above 75% over the visible range, [7][8][9] and its low processing temperatures, <200 C. 10 To demonstrate the applicability of a-IGZO, several prototype devices have already been produced, including both rigid and flexible active matrix organic light emitting diode (AMOLED) displays, [11][12][13] e-ink displays, [14][15][16] and radio frequency identification (RFID) tags. [17][18][19] The deposition of a-IGZO has been investigated through several routes, including pulsed laser deposition (PLD), 2,20 solution processing, [21][22][23] atomic layer deposition (ALD), 24 and sputtering. 8,10,21,[25][26][27][28] It is commonly found that hightemperature post-process annealing has a positive impact on device performance.…”
mentioning
confidence: 99%